2020
DOI: 10.1002/anie.202007187
|View full text |Cite
|
Sign up to set email alerts
|

DMSO‐Enabled Selective Radical O−H Activation of 1,3(4)‐Diols

Abstract: Control of selectivity is one of the central topics in organic chemistry. Although unprecedented alkoxyl-radicalinduced transformations have drawn a lot of attention, compared to selective CÀH activation, selective radical OÀH activation remains less explored. Herein, we report a novel selective radical O À H activation strategy of diols by combining spatial effects with proton-coupled electron transfer (PCET). It was found that DMSO is an essential reagent that enables the regioselective transformation of dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 95 publications
1
26
0
Order By: Relevance
“…Recently, some explorative studies have been performed in utilizing HBs for promoting the conversion of inert hydroxyl substrates and guiding pathways in purpose. For example, the selective activation of the primary hydroxyl group in diol could be accomplished via forming O−H⋅⋅⋅O=S HBs with DMSO as a proton acceptor, which was in favor of the selective alkoxyl radical transformation, rather than occurring β‐scission due to the unselective activation of both two hydroxyl groups [5] . Han et al [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some explorative studies have been performed in utilizing HBs for promoting the conversion of inert hydroxyl substrates and guiding pathways in purpose. For example, the selective activation of the primary hydroxyl group in diol could be accomplished via forming O−H⋅⋅⋅O=S HBs with DMSO as a proton acceptor, which was in favor of the selective alkoxyl radical transformation, rather than occurring β‐scission due to the unselective activation of both two hydroxyl groups [5] . Han et al [6] .…”
Section: Introductionmentioning
confidence: 99%
“…[4] Thedecreased electron cloud density near the proton nucleus might weaken OÀHbonds,thus enhancing the reactivity of hydroxyl groups.Recently,some explorative studies have been performed in utilizing HBs for promoting the conversion of inert hydroxyl substrates and guiding pathways in purpose.F or example,t he selective activation of the primary hydroxyl group in diol could be accomplished via forming OÀH•••O=SHBs with DMSO as aproton acceptor, which was in favor of the selective alkoxyl radical transformation, rather than occurring b-scission due to the unselective activation of both two hydroxyl groups. [5] Han et al [6] presented that the HBs between the alcohol hydroxyl groups and ionic liquid [EMIM]OAc could accelerate the rate-determining step of hydroxyl groups activation, thus significantly promoting the oxidative esterification of inert aliphatic alcohols.I nt he case of heterogeneous catalysis, researchers also found that the surface-grafted nitrogencontaining ligands on EPy/Pt/Al 2 O 3 catalyst could form HBs with specific hydroxyl groups. [7] However,the research of HBs on heterogeneous surface mainly concentrated on the modification of catalyst surface,p romotion of catalytic performance,a nd elimination of negative impacts via pre-converting -OH.…”
Section: Introductionmentioning
confidence: 99%
“…Jiao and coworkers recently applied similar alcohol activation conditions to an aqueous catalyst system for the regioselective O-H homolysis of 1,3-diols in the presence of DMSO as a hydrogenbond acceptor, enabling distal C-C cleavage and 1,4-aryl migration. 63 In 2019, Pan and coworkers disclosed a protocol encompassing a copper and oxazoline catalyst system for alkoxy radical generation and C-O bond formation to access 3a,3a 0bisfuro[2,3-b]indoline scaffolds and 3-alkoxy furoindolines from tryptophol derivatives (Scheme 16). 64 Remarkably, this method does not require exogenous base, initiator, or oxidant, but the use of a dual Cu(I)/Cu(II) catalyst combination and a bisoxazoline ligand has proven to be essential to reaction efficiency.…”
Section: Transition Metal-mediated Homolysismentioning
confidence: 99%
“…Jiao and coworkers recently applied similar alcohol activation conditions to an aqueous catalyst system for the regioselective O–H homolysis of 1,3-diols in the presence of DMSO as a hydrogen-bond acceptor, enabling distal C–C cleavage and 1,4-aryl migration. 63 …”
Section: Transition Metal-mediated Homolysismentioning
confidence: 99%
“…On the other hand, DMSO, serving as an important organic mediator, has attracted much attention owing to its unique properties over the past decade, and the Jiao group has made great contribution in this regard. [ 6 ] In comparison with DMSO, dimethyl sulfide (DMS) as mediator has rarely been reported in synthetic chemistry. Hence, there is great room for the development of DMS as mediator, especially in the cooperation of DMS with anodic electrochemistry in organic chemistry.…”
Section: Background and Originality Contentmentioning
confidence: 99%